Long-term health insurance: Theory meets evidence - Juan Pablo Atal; Hanming Fang; Martin Karlsson; Nicolas R. Ziebarth (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
To insure policyholders against contemporaneous health expenditure shocks and future reclassification risk, long-term health insurance constitutes an alternative to community-rated short-term contracts with an individual mandate. In this paper, we study the German long-term health insurance (GLTHI) from a life-cycle perspective. The GLTHI is one of the few real-world long-term health insurance markets. We first present and discuss insurer regulation, premium setting, and the main market principles of the GLTHI. Then, using unique claims panel data from 620 thousand policyholders over 7 years, we propose a new method to classify and model health transitions. Feeding the empirical inputs into our theoretical model, we assess the welfare effects of the GLTHI over policyholders' lifecycle. We find that GLTHI achieves a high level of welfare against several benchmarks. Finally, we conduct counterfactual policy simulations to illustrate the welfare consequences of integrating GLTHI into a hybrid insurance system similar to the current system in the United States.
Keywords: G22; I11; I18; 330; long-term health insurance; individual private health insurance; reclassification risk; intertemporal incentives; ACG scores; health transitions